The role of intracellular zinc in chromium(VI)-induced oxidative stress, DNA damage and apoptosis - Rudolf, Emil; Cervinka, Miroslav (Chemico-biological interactions, 2006)
Several studies have demonstrated that zinc is required for the optimal functioning of the skin. Changes in intracellular zinc concentrations have been associated with both improved protection of skin cells against various noxious factors as well as with increased susceptibility to external stress. Still, little is known about the role of intracellular zinc in hexavalent chromium (Cr(VI))-induced skin injury. To address this question, the effects of zinc deficiency or supplementation on Cr(VI)-induced cytotoxicity, oxidative stress, DNA injury and cell death were investigated in human diploid dermal fibroblasts during 48 h. Zinc levels in fibroblasts were manipulated by pretreatment of cells with 100 microM ZnSO4 and 4 or 25 microM zinc chelator TPEN. Cr(VI) (50, 10 and 1 microM) was found to produce time- and dose-dependent cytotoxicity resulting in oxidative stress, suppression of antioxidant systems and activation of p53-dependent apoptosis which is reported for the first time in this model in relation to environmental Cr(VI). Increased intracellular zinc partially attenuated Cr(VI)-induced cytotoxicity, oxidative stress and apoptosis by enhancing cellular antioxidant systems while inhibiting Cr(VI)-dependent apoptosis by preventing the activation of caspase-3. Decreased intracellular zinc enhanced cytotoxic effects of all the tested Cr(VI) concentrations, leading to rapid loss of cell membrane integrity and nuclear dispersion--hallmarks of necrosis. These new findings suggest that Cr(VI) as a model environmental toxin may damage in deeper regions residing skin fibroblasts whose susceptibility to such toxin depends among others on their intracellular Zn levels. Further investigation of the impact of Zn status on skin cells as well as any other cell populations exposed to Cr(VI) or other heavy metals is warranted.
Keywords: Cell Survival; buněčná membrána; Oxidative Stress; Apoptosis; oxidační stres; Humans; kaspasy; Glutathione Peroxidase; nádorový supresorový protein p53; Dermis; Zinc; lidé; Antioxidants; proliferace buněk; glutathionperoxidasa; zinek; Caspases; Cells, Cultured; kaspasa 3; Metallothionein; apoptóza; DNA; Chromium; antioxidancia; Caspase 3; chrom; kultivované buňky; Cell Proliferation; škára; poškození DNA; DNA Damage; fibroblasty; Glutathione Reductase; Cell Membrane; glutathionreduktasa; metalothionein; viabilita buněk; Fibroblasts; Tumor Suppressor Protein p53